OPEC and the Oil Market - Pescatori, Andrea (IMF Working Papers; Working Paper ;, 2022)
This paper studies the historical importance of OPEC for oil price fluctuations. An event-study approach is used to identify the effects of OPEC announcements on oil price fluctuations. Results show that price volatility is higher than typical around OPEC meetings. Also, members' compliance, a proxy for credibility, has strongly fluctuated over time. An ordered multinomial logit framework identifies the main factors that explain OPEC's decisions to cut, maintain, or boost members' oil production and is able to successfully predict OPEC meeting outcomes 66 percent of the time, between 1989 and 2019. Cyclical oil price fluctuations (as opposed to persistent shifts in levels) drive OPEC's decisions, suggesting that OPEC's objective is to stabilize the oil price rather than countering fundamental shifts in demand and supply. Low OPEC's market share reduces the probability of a production cut. Finally, the transparency of OPEC's statements has modestly improved between 2002 and 2019.